Tropical Pacific interactions in the WCRP-CMIP3 multi-model dataset - Berman, Ana Laura (2011)
The ability of numerical models in reproducing the observed statistical links between the sea surface temperature of central and eastern tropical Pacific Ocean is analysed in this paper. Significant links in the whole spectrum of frequency were studied for models of the World Climate Research Program (WCRP-CMIP3/IPCC-AR4) using the methodology of wavelet coherence. During the second half of the twentieth century, in-phase or quasi-in-phase links in oscillations of 2–6 years, a lack of relation in oscillations of 8–12 years and time lagged links in the longest periodicities are detected in the observed dataset. Some of the analysed models are able to reproduce the observed relationships in oscillations shorter than 6 years and few of them also reproduce the lacks of significant relation in the band of 8–12 years. On the other hand, all models have serious problems representing the observed time lagged links in the longest waves. The analysis shows that climate models are still unable to reproduce specific features of tropical Pacific interactions with potential effect on the Southern Hemisphere atmospheric circulation and, in particular, the South American climatic variability.